Additional Oil Palm Ash and Nitrogen Fertilizer as Soil Ameliorant for the Oil Palm Seedlings (Elaies guineensis Jacq.) in Pre Nursery Stage - Enita Enita; Eddiwal Eddiwal; Ratnadewi Ratnadewi (Journal of Applied Agricultural Science and Technology, 2025)
Oil palm has high economic value and is one of Indonesia’s most significant contributors to foreign exchange. The management of oil palm seedlings is important in determining their growth and subsequent development in the field. Research on the application of oil palm ash and nitrogen fertilizer was conducted at the pre-nursery stage. This study aims to determine the effects of oil palm ash and nitrogen fertilizer on the growth performance of oil palm seedlings in the pre-nursery stage. The experiment employed a factorial randomized block design with two factors. The first factor was the dose of oil palm ash (A), consisting of A1 = 600 g/g/polybag, A2 = 800 g/g/polybag, A3 = 1000 g/g/polybag. The second factor was the dose of nitrogen fertilizer (N), consisting of N1 = 100 mg/polybag, N2 = 200 mg/polybag, and N3 = 300 mg/polybag. The results showed that the interaction between the dose of oil palm ash and nitrogen fertilizer significantly affected both fresh weight and dry weight of oil palm seedlings. The combination of 1000 g/g/ g/polybag of oil palm ash and 200 mg/polybag of nitrogen fertilizer produced the best growth, yielding 7.77 g/g/plant of fresh weight and 2.39 g/g/plant of dry weight. Based on observation of plant growth, the application of oil palm ash did not show a significant effect on plant height, leaf length, or number of leaves. However, the highest stem diameter was recorded in treatment A2 (0.77 cm), which was significantly different from treatment A3. In contrast, the application of nitrogen fertilizer at a rate of 100 g per (N1) resulted in the lowest plant height (21.70 cm) and the shortest leaf length (17.36 cm), both of which were significantly different from the other treatments. The largest stem diameter was obtained in treatment N2 (0.79 cm), which was substantially different from N1. No significant differences were observed in the number of leaves among the treatments.